Teaching English in Nepal from the Students’ Perspective - Kshetree, Arun Kumar; KC, Kamala; Bhusal, Tilak; Bhandari, Bhim Lal; Jyoti, Rameshwar (Butwal Campus Journal, 2025)
The English Language Teaching (ELT) and learning situation in Nepal is mostly criticized by the general public and the academia for not being as effective as expected by the curriculum. Many research reports and research papers describe that the ELT situation is still satisfactory in Nepal. One of the most relevant evaluators to describe the situation of teaching English is the group of students who stay in the class to learn what the teachers teach in the English classes. This paper is a part of a wide-ranging research accomplished with the Emerging Faculty Research Grant from the Research Coordination and Development Council (RCDC) Rector’s Office, Tribhuvan University. It was conducted with the objective of analyzing the students’ perceptions towards the teachers’ classroom practices and activities. This survey research was based on the information from 400 students studying in 16 secondary schools of Lumbini Province with the help of a questionnaire to rate the activities of the English teachers. The gathered information was sufficient to prove that the ELT situation does not seem to be as it is criticized and it is gradually changing and developing in Nepal that makes us become hopeful for the future. The findings of the study will help developing the ELT situation of Nepal.